الدفاع الشرعي بين الفقه الاسلامي والتشريع الوضعي (Revue El-Wahat pour les Recherches et les Etudes, 2021)
ملخص:يتناول البحث موضوع الدفاع الشرعي دراسة مقارنة بين الفقه الجنائي الاسلامي والتشريع الوضعي، حيث عالج مسألة تعرض الفرد للاعتداء سواء كان مادي أو معنوي، ومدى مشروعية دفعه؛ وهو ما يعرف في القوانين الوضعية بالدفاع المشروع أو الدفاع الشرعي، وفي الفقه الاسلامي بدفع الصائل,فنجد الشريعة الاسلامية سباقة في إباحته وتنظيم أحكامه، إلا أنه وأمام صد الشخص للاعتداء المكفول قانونا لابد عليه ألا يتمادى في الرد حتى لا يخرج عما هو مسموح له قانونا وهو ما أقره المشرع الجزائري من خلال قانون العقوبات والمعبر عنها بحالة التناسب والتلازم بين الاعتداء ورد الاعتداء.الكلمات الدالة: الدفاع الشرعي، الفقه الاسلامي، التشريع الوضعي، الدفاع، الاعتداء.  Abstract: This Research Treats The Subject Of Legitimate Defense, It Is A Comparative Study Between Islamic Criminal Jurisprudence And Positive Law, And They  Include  The Matter  Of Whether An The Person  Was Physically Or Physically Attacked And The Legality Of His Avoiding In Positive Laws,  Wich Was Known As Legitimate Defense, And In Islamic Doctrine By Al- Sael Defensewe Find The Islamic Shariaa Has Been Forerunner To Legalized And Organized Its Provitions  However, In The Face Of The Fact That A Person Is Repulsed By The Legally Guaranteed Attack, He Must Not Continue To Respond So That He Does Not Deviate From What Is Legally Permitted. This Fact Is Approved By The Algerian Legislator Through The Penal Code, Which Is Expressed In The State Of Proportionality And The Correlation Between The Attack And The Response Key Words:  Legal Defense, Islamic Jurisprudence, Positive Legislation, , Defense, Assault.